2020
DOI: 10.1111/ocr.12458
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial clefts in low‐ and middle‐income countries: A scoping review of quality and quantity of research based on literature between 2010‐2019

Abstract: Structured Abstract This paper assesses the research literature on OFC in LMIC over the last decade across various geographical settings and project focus of the indexed literature. A scoping review of the indexed literature was performed using a set of predefined keywords. The articles were filtered by a ten‐year time frame (2010‐2019) and a strict inclusive‐exclusive criterion. Two authors screened the titles/abstracts/full text of the final included papers and input the desired data (year of publication, ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Previous study exhibited great inequalities in HIC versus LMIC peer‐reviewed publications in cleft field over the last 10 years 8 . Like other areas of medical research, cleft research is also characterized by inequalities between HIC and LMIC due to differences in various aspects but mainly in research capacity and infrastructure of comprehensive data of birth defect surveillance systems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study exhibited great inequalities in HIC versus LMIC peer‐reviewed publications in cleft field over the last 10 years 8 . Like other areas of medical research, cleft research is also characterized by inequalities between HIC and LMIC due to differences in various aspects but mainly in research capacity and infrastructure of comprehensive data of birth defect surveillance systems.…”
Section: Discussionmentioning
confidence: 99%
“…4 A study which mapped the OFC research in indexed literature found inequalities in terms of number of publications produced in HIC and LMIC. 5 These discrepancies may be attributed to a lack of research expertise and insufficient emphasis from governmental research funders on prioritizing OFC research.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with cleft lip and palate (CL/P) require a complex and multidisciplinary approach to care that makes sustainable access in low-and middle-income countries (LMICs) challenging. 1 CL/P represents the most common congenital craniofacial deformity with a global prevalence of one in 1000 to 1500. 2,3 It has been well demonstrated that a child on the cleft care continuum should receive care and support at every point in their development to address the complex medical and surgical needs as they reach adulthood.…”
Section: Introductionmentioning
confidence: 99%